EVALUATION OF USER SATISFACTION FOR PASSER BORDER INFORMATION SYSTEM THE STATE OF INDONESIA AND TIMOR-LESTE - Fransiskus Mario Hartono Tjiptabudi; Skolastika Siba Igon; Raul Bernardino (Faculty of Computer Science Universitas Indonesia, 2018)
The administrative process that had previously applied to the cross border Post or ‘Pos Lintas Batas Negara (PLBN)’ is integrated with the way of manuscript the passport data information or ‘Pas Lintas Batas (PLB)’-special card for habitants whereas living a long site of the both coutries border (Indonesia and Timor-Leste), information on a card and then do a recapitulation. This manuscript administration gave unfavourable result such as not have proper archiving in the filing cabinet and difficulty of the search data for the report purpose. To solve these problems, then it has been developed and implemented an application which called ‘Sistem Informasi Pelintas Batas Wilayah Negara (SINTASWIN).’ This Sintaswin application is applied to the immigration authorities in order to record and control the border crosser (traveler). This system will support the national policies and strategies of the Government in managing boarder region. However, the implementation of any application system has it constraints; therefore it needs to be evaluated such as to evaluate end user satisfaction. This study aims to evaluate the satisfaction of users by applying End User Computing Satisfaction (EUCS) methods in order to produce recommendations for the improvement and system development in the future.